Characteristics and prognostic factors of colorectal mucinous adenocarcinoma with signet ring cells - Kong, Xiangquan (Cancer Manag Res, 2017)
BACKGROUND: Colorectal signet ring cell (SRC) carcinoma occurs rarely with a poor prognosis. The present study assessed the prognostic factors and predictive value of SRC ratio in colorectal mucinous adenocarcinoma (MAC) with SRCs (MAC-SRC). PATIENTS AND METHODS: A total of 95 consecutive colorectal MAC-SRC patients, confirmed pathologically from February 1987 to December 2015, were analyzed retrospectively in our institute. Clinical characteristics, pathological grade, TNM staging, and SRC ratio were assessed to identify the prognostic factors related to progression-free survival (PFS) and overall survival (OS). SPSS 22.0 was used for statistical analyses. RESULTS: The median follow-up time was 29.7 months (range 0.8–165). Meanwhile, 5-year PFS and OS rates were 25.6% (95% confidence interval [CI] 16.192–35.008%) and 40.5% (95% CI 29.524–51.476%), respectively. Among the 81 patients who underwent surgery, 78 (96.3%) were diagnosed as stage T3 or T4; 74 (91.4%) showed lymph node involvement, and 27 (29.3%) presented distant metastasis. Metastases of the peritoneal cavity and ovaries were observed commonly in colorectal MAC-SRC. In the multivariate Cox regression model, SRC ratio ≥35%, absence of preoperative radiotherapy, and distant metastasis were independent predictors of PFS. Furthermore, SRC ratio ≥35%, absence of preoperative chemotherapy (pre-CT), and distant metastasis were independent risk factors for poor prognosis. CONCLUSION: A long-term follow-up of colorectal MAC-SRC reveals that it is a rare subtype of colorectal MAC with a dismal prognosis. Furthermore, SRC ratio, pre-CT, and M stage seem to affect OS independently.